Recovering Religious Concepts - Phillips, D. author. aut Link
XII, 272 p.
Keywords: Here it is argued that we need to recover concepts from the distortions of philosophy. In this collection the author shows the disastrous consequences for an understanding of religion of the epistemic divides which can be found in contemporary philosophy of religion; divides between belief and practice, the world and God, religious experience and religious contexts. By closing these divides religious significance is given its proper place.